Dietary Lagenaria siceraria fruit improves growth, gene expression, histology, and immune-antioxidant defense to overcome the Fusarium solani challenge in Litopenaeus vannamei - Moaheda E.H. Eissa; Ehab El-Haroun; Hanan Mohammed Rashwan; Zulhisyam Abdul Kari; Roshmon Thomas Mathew; Dalal Sulaiman Alshaya; Najah M. Albaqami; Layla A. Almutairi; Sultan Mohammed Areshi; Mada M. AL-Qurashi; Yasmin M. Abd El-Aziz; El-Sayed Hemdan Eissa; et al. (Aquaculture Reports, 2025)
For the sustained output in shrimp farming, optimizing disease resistance and health is essential. The medicinal plant Lagenaria siceraria (LS), often known as bottle gourd, has pharmacological characteristics that involve immune-modulation. It is hypothesized that dietary LS supplementation may be able to enhance growth and interrelated immune-antioxidant response to combat Fusarium solani infection in juvenile Pacific white-leg shrimp (Litopeneaus vannamei). For 70 days, shrimp (initial weight: 4.50 ± 0.10 g; n = 60/treatment) were randomly stocked into four treatments fed on LS-diets with 0, 10, 20, and 30 g LS/kg diet (LS0, LS10, LS20, and LS30), respectively. Dietary LS enrichment improved growth and feed efficiency variables as well as fish survival. The most favorable outcomes were in the LS10 diet. The ash content and amylase activity were enhanced by LS supplementation. A level-dependent boosting effect of LS-fortified diets on lipase activity, immune and antioxidant response in terms of total hemocyte count, lysozyme, phenoloxidase, catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase besides up-regulation of lysozyme, prophenoloxidase, CAT and SOD genes. In addition, a gradual increase in the diameters of muscle fibers and the number and volume of B-cells of hepato-pancreatic tissues by dietary LS enrichment. Following the F. solani challenge, dietary LS addition enhanced shrimp survival rate, where it was 60, 60, and 70 % in the LS10, LS20, and LS30 groups, respectively, compared with the LS0 group (35 %). Overall, this investigation offers insightful knowledge about LS's potential as a dietary intervention to enhance the immune status, disease resistance, and growth of L. vannamei, which represents a major accomplishment in shrimp aquaculture.